The case for connecting the implementation of the Paris Climate Agreement and the 2030 Agenda for Sustainable Development - Clara Brandi; Adis Dzebo; Hannah Janetschek (Deutsches Institut für Entwicklungspolitik (DIE), 2017)
The adoption of the 2030 Agenda for Sustainable Development and the conclusion of the Paris Agreement in the closing months of 2015 represented a significant moment in the global movement towards sustainability. There is enormous potential for co-benefits to arise from the mutually supportive implementation processes of the 17 Sustainable Development Goals (SDGs) elaborated in the 2030 Agenda and the Nationally Determined Contributions (NDCs) underpinning the legally binding Paris Agreement. Countries' NDCs, their climate plans, include not only commitments to mitigate emissions but also address many other themes relevant to sustainable development. We present key findings of a fine-grained analysis of how climate activities in the NDCs contribute to SDGs and their targets. Under the provisions of the Paris Agreement, countries will submit an updated NDC every five years, the intention being that they scale-up their ambitions. The first full review (“global stocktake”) will occur in 2023, but an initial stocktaking exercise will take place in 2018 (“facilitative dialogue”). Implementation of the 2030 Agenda is based on national sustainable development (SD) strategies that vary from country to country. At the global level, Follow-Up and Review mechanisms take place during the annual High Level Political Forum (HLPF) at the United Nations in New York. As a rule, these two implementation processes are kept separate, despite the many existing thematic overlaps and the shared objective of achieving global SD, but our analysis emphasises that the climate activities in the NDCs can support the achievement of a multitude of SDGs and their targets. They not only cover themes relevant to SDG 13 but also many other important fields of sustainable development. NDC climate activities also underline the interlinked character of the SDGs. In fact, numerous NDC climate activities entail synergies that can promote several SDGs at once. To generate co-benefits, NDC and SDG implementation processes should be coordinated 1) to prevent duplication and thereby reduce the costs, and 2) to achieve a more systematic implementation of the 2030 Agenda at country level that utilises already committed activities in NDCs to leverage synergies between both agendas. Moving forward, the opportunity to connect the Paris Agreement and the 2030 Agenda should be considered in order to promote policy coherence by maximising co-benefits and systematically mediating trade-offs for a more efficient implementation: - In the context of the Paris Agreement, countries should use future NDC updates to more closely align their climate activities with the SDGs. - In the context of the 2030 Agenda, SD strategies should meaningfully complement NDCs. - Co-benefits have the potential to increase the motivation for countries to fulfil commitments, but trade-offs should be anticipated early on in order to implement both agendas more effectively.
Keywords: 330; Klimawandel; Agenda 2030